Managing Talent in the Digital Age: Implications for Generation Z Engagement and Satisfaction - Novialumi, Anita; Rahmaningsih, Dinda Pradita; Sukirno, Sukirno (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2026)
This study examines the effects of recruitment and selection, teamwork and management support, performance and career management, as well as income and compensation, on work engagement and job satisfaction among Generation Z employees in the digital era. The study involved 62 employees working in a food and beverage company in the Cikarang–Bekasi area, selected using a census sampling technique. Data were analyzed using descriptive methods and path analysis with Partial Least Squares–Structural Equation Modeling (PLS-SEM). Data were collected through an online survey distributed via Google Forms, consisting of 35 items measured on a five-point Likert scale. The results indicate that: salary and compensation, performance and career management, teamwork and management support, and recruitment and selection positively affect employees’ work engagement; these factors also have a positive effect on employees’ job satisfaction; and work engagement positively influences employees’ job satisfaction.